Overview of the Level of Basic Life Support Knowledge in Members of the Humanitarian Student Activities Unit - Handayani, Audia; Emaliyawati, Etika; Mirwanti, Ristina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cardiac arrest is a sudden cessation of heart activity that requires immediate treatment in the form of Basic Life Support (BLS). Students who are members of the Student Activity Unit (UKM) in the humanitarian field at Unpad are potential first aiders to provide basic life support in the event of cardiac arrest. This study aims to determine the level of knowledge of basic life support in students who are members of UKM in the humanitarian field at Universitas Padjadjaran. The method used in this research is quantitative descriptive with a cross sectional approach. The population in this study amounted to 158 active members of the humanitarian student activity unit and the sample was taken using convenience sampling type (n = 120). Data were collected using a questionnaire containing 30 questions that have been declared valid and reliable with a Cronbach's alpha value of 0.797 and data were analysed using computer software with univariate analysis techniques. The results showed that the level of knowledge of humanitarian UKM members at Unpad regarding basic life support was classified into the good category with a total of 108 respondents (90%). The conclusion in this study is that the level of knowledge of basic life support in members of humanitarian UKM at Universitas Padjadjaran is in the good category, but it is necessary to increase knowledge, especially on procedural topics related to basic life support.